In vitro germination and embryo rescue of Lepidium campestre hybrids - Fahlgren, David (SLU/Dept. of Biosystems and Technology (from 130101), 2014)
Lepidium species are members of the Brassicaceae family, in which some commercial oil crops belong to and these species are wild. In an effort for domesticating a new oil crop that started about 20 years ago, Lepidium campestre has been chosen as a target as it is cold hardy and has high seed yield potential. However, L. campestre contains low oil content and has pod shatter problem. To solve these problems, crosses between different Lepidium species have been previously carried out. In this project, a laboratory study with the aim of facilitating the germination of L. campestre x L. draba hybrid seeds in vitro and embryo rescue of hybrids between L. campestre x L. graminifolium was conducted. Different types of medium were tested both for germination and for embryo rescue. There was no significant difference in the germination rate between nine different germination media when using the old storage seeds of L. campestre. The hybrid seeds did not germinate on the germination media tested. In the embryo rescue experiment, one of the parental ovule grew on the medium containing 0.1mg/l NAA and 1.5mg/l BAP. Several ovules of parental and hybrid seeds turned brown on the other media including the abovementioned medium. Two hybrid ovules produced callus on the medium containing 0.5 mg/l TDZ and 0.01mg/l NAA and one grew on the medium containing 0.1mg/l TDZ and 0.5mg/l NAA. The hybrid ovaries grew larger after 7 days, four of them become infected with fungi after 16-17 days and were therefor removed, several of the parental ovaries produced callus on their basal end.